2022
DOI: 10.1093/mnras/stac2457
|View full text |Cite
|
Sign up to set email alerts
|

Period–colour and amplitude–colour relations for OGLE-δ Scuti stars in the Galactic bulge and LMC

Abstract: We present an analysis on the behaviour of the Galactic bulge and the Large Magellanic Cloud (LMC) δ Scuti stars in terms of period-colour and amplitude-colour (PCAC) relations at maximum, mean and minimum light. The publicly available Optical Gravitational Lensing Experiment-IV (OGLE-IV) light curves for Galactic bulge and OGLE-III light curves for LMC δ Scuti stars are exploited for the analysis. It has been found that the Galactic bulge δ Scuti stars obey flat PC relations at maximum/mean/minimum light whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, Deka et al (2022) studied 3202 δ Sct stars in the Galactic bulge from the OGLE-IV catalogue (Soszyński et al 2021) and the Large Magellanic Cloud (LMC) from OGLE-III. Their analysis revealed a broken PLR for the bulge δ Sct stars, but not for those in the LMC.…”
Section: Previous Plrs For δ Sct Starsmentioning
confidence: 99%
“…Furthermore, Deka et al (2022) studied 3202 δ Sct stars in the Galactic bulge from the OGLE-IV catalogue (Soszyński et al 2021) and the Large Magellanic Cloud (LMC) from OGLE-III. Their analysis revealed a broken PLR for the bulge δ Sct stars, but not for those in the LMC.…”
Section: Previous Plrs For δ Sct Starsmentioning
confidence: 99%
“…The computational codes and numerical methods as described in Yecko et al (1998) and Kolláth et al (2002) were used in those studies to carry out the pulsation modelings. Recently, using -, Das et al ( 2020) presented theoretical explanations of the observed PC and AC relations at maximum and minimum light for the pulsating stars such as RR Lyraes, type I and type II Cepheids, whereas the same was provided for the Scuti stars by Deka et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical pulsation properties of Cepheid variables have been investigated by Bono and his group in the 1990s (Bono et al 1998(Bono et al , 1999(Bono et al , 2000Caputo et al 2000a,b). The comparison between the observed and theoretical period-color (PC), amplitude-color (AC) and period-luminosity (PL) relations for Cepheids, RR Lyraes, and δ Scuti stars in the Galaxy and the Magellanic Clouds in the literature were mostly done at maximum, minimum, and mean light (Kanbur et al 2004;Kanbur and Ngeow 2006;Kanbur et al 2007;Das et al 2020;De Somma et al 2020;Deka et al 2022;De Somma et al 2022). However, the relation at mean light is the average of the relations at all phases, hence, investigating the Cepheid PL/PC relations at other phases of the stars provides a better understanding of the pulsational properties of the stars.…”
Section: Introductionmentioning
confidence: 99%